Central Retinal Vein Occlusion: A Rare Ocular Complication of Inflammatory Bowel Disease—A Case Series. Issue 9 (26th April 2019) - Choi, Harry; Bou-Abboud Matta, Carine; Fu, Gregory; Trichonas, Georgios; Morgan, Michael L; Yursky, Mary; Katz, Jeffry; Sinh, Preetika
Abstract : Inflammatory bowel disease can present with multiple ocular manifestations, including episcleritis, scleritis, and uveitis (supplementary data [1]). The incidence of ophthalmological complications in patients with inflammatory bowel disease varies from 3.5% to 11.8% (supplementary data [2]). We present 3 rare cases of central retinal vein occlusion associated with ulcerative colitis.